Update on the advances and challenges in bioequivalence testing methods for complex topical generic products - Alomari, Nedaa; Alhussaini, Waleed (Frontiers in Pharmacology, 2024)
Most of the government regulatory agencies including the United States Food and Drug Administration and European Medicine Agency demand that the generic complex topical products prove pharmaceutical and bioequivalence. The evaluation of bioequivalence for complex topical dermatological formulations is a challenging task that requires careful consideration of several factors. Although comparative clinical studies are still considered the gold standard approach for establishing bioequivalence in most formulations, these studies can be costly and insensitive to detect formulation differences. Therefore, significant efforts have been made to develop and validate alternative approaches that demonstrate bioequivalence and expedite the availability of high-quality generic topical dermatological products. This article reviews current methods for determining the bioequivalence of topical formulations in humans with particular emphasis on recent advances in these methodologies. Most of the alternative methods are sensitive and reproducible with the capability to ease the financial burden of comparative clinical studies in a short delivery time. Limitations associated with each technique are reviewed in detail.